The Influence of Investment Decisions, Profitability, Capital Structure, and Company Size on the Value of Property and Real Estate Companies on the IDX - Uz-zaky, Muhammad Raffi; Suhardi, Suhardi; Deseria, Rita (Trigin Publisher, 2024)
This study analyses the influence of investment decisions, profitability, capital structure, and company size on the property and real estate companies on the Indonesia Stock Exchange (2020-2024). Using multiple linear regression on secondary data, the results concluded that investment decisions, profitability, and company size have a significant influence on the value of companies in the property and real estate sectors, while capital structure is insignificant. The capital structure is insignificant, supported by Modigliani-Miller's theory and pandemic policy interventions that reduce debt risk. The findings reinforce the role of signaling theory where profitability is the main signal of investor confidence, while capital structure is irrelevant in the context of emerging markets. Future research recommendations include the integration of sustainability variables (ESG), longitudinal analysis of the impact of post-pandemic debt restructuring, as well as qualitative approaches to unravel the paradox of company size. The practical implications suggest optimizing profitability through operational efficiency and prudence in large-scale business expansion. Future research will need to expand variables such as ESG performance, dividend policies, or environmental risks to answer unexplained variations. Capital structural analysis can be focused on specific conditions (e.g., property cycle phases or high interest rates) using a moderated regression approach. Longitudinal studies are needed to assess the long-term impact of pandemic policies, while qualitative methods (interviews) can uncover the paradox of the negative influence of company size. Inter-sector comparisons and non-linear modeling are also recommended to understand the complexity of variable relationships in asset-heavy contexts such as properties